The effect of hydrotherapy and land-based rehabilitation program combined with ankle taping on ankle functional ability and the number of re-injury in athletes with chronic ankle instability - Poonyanat Nualon (Chulalongkorn University, 2013)
Thesis (Ph.D)--Chulalongkorn University, 2010